Alpha-1 antitrypsin augmentation therapy decreases miR-199a-5p, miR-598 and miR-320a expression in monocytes via inhibition of NFκB - Hassan, Tidi (Sci Rep, 2017)
Alpha-1 antitrypsin (AAT) augmentation therapy involves infusion of plasma-purified AAT to AAT deficient individuals. Whether treatment affects microRNA expression has not been investigated. This study’s objectives were to evaluate the effect of AAT augmentation therapy on altered miRNA expression in monocytes and investigate the mechanism. Monocytes were isolated from non-AAT deficient (MM) and AAT deficient (ZZ) individuals, and ZZs receiving AAT. mRNA (qRT-PCR, microarray), miRNA (miRNA profiling, qRT-PCR), and protein (western blotting) analyses were performed. Twenty one miRNAs were differentially expressed 3-fold between ZZs and MMs. miRNA validation studies demonstrated that in ZZ monocytes receiving AAT levels of miR-199a-5p, miR-598 and miR-320a, which are predicted to be regulated by NFκB, were restored to levels similar to MMs. Validated targets co-regulated by these miRNAs were reciprocally increased in ZZs receiving AAT in vivo and in vitro. Expression of these miRNAs could be increased in ZZ monocytes treated ex vivo with an NFκB agonist and decreased by NFκB inhibition. p50 and p65 mRNA and protein were significantly lower in ZZs receiving AAT than untreated ZZs. AAT augmentation therapy inhibits NFκB and decreases miR-199a-5p, miR-598 and miR-320a in ZZ monocytes. These NFκB-inhibitory properties may contribute to the anti-inflammatory effects of AAT augmentation therapy.